2019
DOI: 10.1038/s41594-019-0297-8
|View full text |Cite
|
Sign up to set email alerts
|

The molecular mechanism of cotranslational membrane protein recognition and targeting by SecA

Abstract: Cotranslational protein targeting is a conserved process for membrane protein biogenesis. In Escherichia coli, the essential ATPase SecA was found to cotranslationally target a subset of nascent membrane proteins to the SecYEG translocase at the plasma membrane. The molecular mechanism of this pathway remains unclear. Here we use biochemical and cryoelectron microscopy analyses to show that the N-terminal amphipathic helix of SecA and the ribosomal protein uL23 form a composite binding site for the transmembra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 65 publications
2
32
0
Order By: Relevance
“…A co-translational targeting by SecA has been observed for the inner membrane protein RodZ, which contains a large cytosolic domain preceding its single transmembrane domain ( Rawat et al, 2015 ; Wang et al, 2017 ), and for the periplasmic maltose binding protein MBP ( Huber et al, 2017 ). This is in line with the ability of SecA to interact with translating and non-translating ribosomes ( Eisner et al, 2003 ; Karamyshev and Johnson, 2005 ; Huber et al, 2011 ; Knupffer et al, 2019 ; Origi et al, 2019 ; Wang S. et al, 2019 ). On the other hand, a post-translational interaction of SRP has been shown for the small bacterial membrane proteins YohP and YkgR ( Steinberg et al, 2020 ) and for the tail-anchored proteins DjlC, Flk, and SciP ( Pross et al, 2016 ; Peschke et al, 2018 ).…”
Section: Targeting the Secyeg Transloconsupporting
confidence: 76%
“…A co-translational targeting by SecA has been observed for the inner membrane protein RodZ, which contains a large cytosolic domain preceding its single transmembrane domain ( Rawat et al, 2015 ; Wang et al, 2017 ), and for the periplasmic maltose binding protein MBP ( Huber et al, 2017 ). This is in line with the ability of SecA to interact with translating and non-translating ribosomes ( Eisner et al, 2003 ; Karamyshev and Johnson, 2005 ; Huber et al, 2011 ; Knupffer et al, 2019 ; Origi et al, 2019 ; Wang S. et al, 2019 ). On the other hand, a post-translational interaction of SRP has been shown for the small bacterial membrane proteins YohP and YkgR ( Steinberg et al, 2020 ) and for the tail-anchored proteins DjlC, Flk, and SciP ( Pross et al, 2016 ; Peschke et al, 2018 ).…”
Section: Targeting the Secyeg Transloconsupporting
confidence: 76%
“…It is intimately associated with the SecYEG translocon, and it uses ATP to drive post-translational polypeptides through the pore into the periplasm [reviewed by (26)]. Recent work has shown that SecA mimics the properties of the SRP (90,91). Thus, the use of superfamily 2 proteins for polypeptide translocation across membranes may be conserved throughout evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular docking is one of the most benefit and theoretical tools to predict the structure of complexes formed by small‐molecule ligand and protein (Du et al, 2016; Kosol et al, 2019; Lyu et al, 2019; S. Wang et al, 2019). We then use molecular simulation to further reveal the detailed interaction model between shikonin and IMPDH2.…”
Section: Resultsmentioning
confidence: 99%